Interhemispheric effects of iTBS on the fronto-parietal network: Evidence from dual-site stimulation - Isabell Int-Veen; Beatrix Barth; Ramona Täglich; Betti Schopp; Hans-Christoph Nuerk; Christian Plewnia; Stefanie De Smet; Marie-Anne Vanderhasselt; Andreas J. Fallgatter; Ann-Christine Ehlis; David Rosenbaum (Neurobiology of Stress, 2025)
This study investigated the neuromodulatory effects of Theta Burst Stimulation (TBS) on resting-state functional connectivity (FC) following psychosocial stress induced by the Trier Social Stress Test (TSST). Given its key role in cognitive control and emotion regulation — processes highly relevant for rumination — we focused on the frontoparietal network. Across two studies, intermittent (iTBS) and continuous (cTBS) protocols were applied to the left Dorsolateral Prefrontal Cortex (DLPFC; study 1) and right Ventrolateral Prefrontal Cortex (VLPFC; study 2) prior to stress induction. Functional Near-Infrared Spectroscopy (fNIRS) was used to assess neural changes. A total of 88 (study 1) and 89 (study 2) healthy participants were recruited, balanced for low and high trait rumination. Each participant received both active and sham TBS (iTBS or cTBS), in a randomized, counterbalanced design. Results indicated that iTBS elicited excitatory effects on prefrontal and fronto-parietal connectivity, whereas cTBS effects were more variable. Trait rumination emerged as a modulator of TBS effects: In study 1, significant interactions for FC between the right VLPFC and Somatosensory Association Cortex (SAC) when stimulating the left DLPFC emerged, while study 2 revealed similar interactions for FC between the left DLPFC and SAC and intra-SAC FC when stimulating the right VLPFC. Correlations between post-stress state rumination and FC changes further support these findings. These results underscore the importance of neural assessments in TBS research and highlight the complexity of individual differences in state and trait rumination. Understanding the interplay between TBS, fronto-parietal connectivity, and rumination may provide valuable insights into personalized neuromodulation strategies.